Moldable antibacterial composite hydrogel loaded with iodine nanosheets and preparation method thereof

Through the shaped antibacterial composite hydrogel loaded with iodine nanosheets, the bacterial resistance, local disinfection effect and high price of existing antibacterial materials are solved, and efficient and lasting antibacterial effects are achieved, and a variety of high-quality antibacterial effects are achieved. Excellent performance.

CN119455077APending Publication Date: 2025-02-18XUZHOU MEDICAL UNIVERSITY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411681504.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Existing antibacterial materials have problems such as bacterial resistance, local disinfection effect is not lasting, high price and delayed effectiveness, and it is difficult to continuously and effectively inhibit bacterial infection in clinical practice.

Method used

Using a shaped-shaped antibacterial composite hydrogel loaded with iodine nanosheets, the shaped-shaped antibacterial composite hydrogel is formed by preparing an iodine nanosheet suspension and a shaped-shaped composite hydrogel precursor solution, combining tannin acid and borax to form an I2/PBST shaped-shaped antibacterial composite hydrogel. .

Benefits of technology

This composite hydrogel not only has antibacterial effects, reduces the probability of bacterial infection and is not bacterial resistance, but also has plasticity, stretchability, self-healing, adhesion and biodegradability, and is suitable for filling defect areas with different shapes and Strong attachment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119455077A_ABST
    Figure CN119455077A_ABST
Patent Text Reader

Abstract

The preparation method comprises the following steps: grinding an iodine block to obtain iodine powder, adding the iodine powder into double distilled water, and carrying out ultrasonic stripping to obtain an iodine nanosheet suspension; under the conditions of stirring and water bath heating, dissolving polyvinyl alcohol with double distilled water to obtain a polyvinyl alcohol solution, adding sodium alginate in batches, and continuously stirring in a water bath to obtain a moldable composite hydrogel precursor solution; dissolving tannic acid by adopting an iodine nanosheet suspension, then adding into the moldable composite hydrogel precursor solution, uniformly stirring at room temperature, adjusting the pH value of the solution to be neutral, finally dropwise adding a borax solution, and stirring into gel to obtain the I2 / PBST moldable antibacterial composite hydrogel. The prepared composite hydrogel not only can play an antibacterial role and reduce the bacterial infection probability of infection sites, but also has excellent properties such as plasticity, stretchability, self-healing property, adhesion and degradability, is convenient to fill defect parts with different shapes, and is firm in adhesion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of biomedical materials, and in particular relates to a plastic antibacterial composite hydrogel loaded with iodine nanosheets and a preparation method thereof. Background Art

[0002] At present, the commonly used antibacterial drug materials in clinical practice include antibiotics, iodine solution, chlorhexidine, hydrogen peroxide, and inorganic metal ions, but they have the following disadvantages: antibiotics are widely used in infected defects, but long-term use of antibiotics can lead to the generation of bacterial resistance, which is not conducive to continuous anti-inflammatory treatment. As a common disinfectant in clinical practice, iodine solution is widely used for disinfection of skin and mucous membranes because of its good biocompatibility, broad-spectrum bactericidal effect and low cost. However, due to its poor solubility and volatility, iodine solution cannot have sufficient concentration of iodine solution in the local disinfection site for a long time, which leads to its inability to act on tissues as a drug for continuous bactericidal effect. Chlorhexidine solution contains a small amount of odorized alkyl trimethyl iron, which can effectively fight most Gram-positive and Gram-negative bacteria. They are often used in trauma or other open wounds in operating rooms, but their effect will be weakened in the presence of blood. Hydrogen peroxide is an oxidant that can trigger the ionization of molecules or atoms in bacterial cells, thereby breaking the lipid chains on the cell wall and destroying the cell wall; however, hydrogen peroxide can damage new epithelial tissue and cause rashes on the surrounding skin; if the above preparations are applied under pressure or in deep wounds, oxygen bubbles will enter the blood vessels to form gas emboli and threaten the patient's life. Inorganic metal ions mainly refer to metals such as silver, copper, and zinc or their ions, which are attached to porous materials using physical adsorption ion exchange methods, and use the antibacterial ability of metal ions to achieve the purpose of long-term antibacterial through sustained release; the disadvantages are that they are relatively expensive and have a delayed antibacterial effect, and cannot kill bacteria as quickly as organic antibacterial agents, and have almost no inhibitory effect on fungi and molds.

[0003] Hydrogel is a polymer network system with a hydrophilic three-dimensional mesh cross-linked structure that can absorb and retain a large volume of water. Hydrogel is soft in nature, and different functions can be achieved by regulating the components and structure of the hydrogel. It is an excellent material for wound dressings. According to actual clinical needs, hydrogel dressings can be given good biocompatibility and biodegradability, while also having self-healing, adhesion, antibacterial and antioxidant properties. Due to its loose and porous internal structure, hydrogel can also be used as a carrier for drugs or other biologically active substances. Summary of the invention

[0004] The purpose of the present invention is to provide a plastic antibacterial composite hydrogel loaded with iodine nanosheets and a preparation method thereof. The preparation method is simple. The prepared composite hydrogel can, on the one hand, exert an antibacterial effect, reduce the probability of bacterial infection at the infection site and has no bacterial resistance; on the other hand, it can have excellent properties such as plasticity, stretchability, self-healing, adhesion, and degradability, which is convenient for filling defect sites of various shapes and has firm adhesion.

[0005] To achieve the above object, the technical solution adopted by the present invention is: a plastic antibacterial composite hydrogel loaded with iodine nanosheets and a preparation method thereof, comprising the following steps:

[0006] S1. preparing an iodine nanosheet suspension: fully grinding an iodine block to obtain iodine powder, adding the iodine powder to double distilled water, and ultrasonically exfoliating to obtain an iodine nanosheet suspension;

[0007] S2. Preparing a plastic composite hydrogel precursor solution: dissolving polyvinyl alcohol with double distilled water at 85 to 95° C. under stirring and heating in a water bath at 85 to 95° C., and obtaining a polyvinyl alcohol solution after the polyvinyl alcohol is completely dissolved, adding sodium alginate in batches, and continuing to stir in a water bath at 85 to 95° C. for 0.5 to 1.5 h to obtain a plastic composite hydrogel precursor solution;

[0008] S3, using the iodine nanosheet suspension prepared in step S1 to dissolve tannic acid to obtain a tannic acid-I2 composite solution, then adding the tannic acid-I2 composite solution to the plastic composite hydrogel precursor solution prepared in step S2, stirring evenly at room temperature, and adjusting the pH value of the solution to neutral;

[0009] S4, adding borax solution to the solution obtained in step S3 and stirring to form a gel to obtain I2 / PBST shapeable antibacterial composite hydrogel.

[0010] Preferably, in step S1, the concentration of the iodine nanosheet suspension is 5 mg / mL; the suspension is placed in an ultrasonic cleaner for ultrasonic peeling for 4 hours.

[0011] Preferably, in step S2, the mass fraction of the polyvinyl alcohol solution is 8%; the mass volume ratio between the sodium alginate and the polyvinyl alcohol solution is 30 mg:1.06 mL.

[0012] Preferably, in step S2, polyvinyl alcohol is dissolved in 90°C double distilled water under stirring and heating in a 90°C water bath, and after the polyvinyl alcohol is completely dissolved, sodium alginate is added in batches, and stirring is continued in a 90°C water bath for 1 hour to obtain a shapeable composite hydrogel precursor solution.

[0013] Preferably, in step S3, the concentration of the tannic acid-I2 composite solution is 40 mg / mL; and the volume ratio between the tannic acid-I2 composite solution and the shapeable composite hydrogel precursor solution is 1:2.65.

[0014] Preferably, in step S4, the concentration of the borax solution is 29 mg / mL; the volume ratio between the borax solution and the shapeable composite hydrogel precursor solution in step S2 is 1:3.53.

[0015] To achieve the above object, the present invention also provides a plastic antibacterial composite hydrogel loaded with iodine nanosheets prepared by the above preparation method.

[0016] Compared with the prior art, the present invention has the following beneficial effects:

[0017] (1) The hydrogel in the present invention is a unique three-dimensional network polymer, and its structure is similar to that of the natural extracellular matrix. Therefore, the hydrogel material can provide support and metabolic space for cell adhesion, proliferation, and growth. The hydrogel's water absorption and swelling characteristics and the osmotic diffusion of small molecules make it have good biocompatibility. The network of borax-polyvinyl alcohol hydrogel is mainly connected by the borax ester bond between the cis-diol site of the polyvinyl alcohol chain and the borax. Sodium alginate is an abundant biopolysaccharide with good biocompatibility and biodegradability. When added to the hydrogel system, it can significantly increase the mechanical properties of the hydrogel and has excellent coagulant and hemostatic properties in the tissue. Tannic acid is a plant-derived polyphenol compound rich in catechol groups and has good adhesive properties. In the polyvinyl alcohol-sodium alginate-tannic acid-borax composite hydrogel system, sodium alginate and tannic acid are connected to the borax-polyvinyl alcohol network by hydrogen bonds. Due to the dynamically reversible hydrogen bonds and borax ester bonds, the composite hydrogel exhibits self-healing ability. The composite hydrogel has good mechanical strength, self-adhesive properties, remodelability, good biocompatibility and biodegradability, and is a good biological embedding scaffold material.

[0018] (2) The iodine nanosheets in the present invention are a two-dimensional nanostructured material, which increases the surface area for interaction with bacteria compared to iodine solution, thereby improving the efficiency of the reaction with bacteria. The iodine nanosheets have good stability in vitro and show excellent biodegradability when in contact with cell culture; at the same time, they use the H2O2 produced by bacteria for allotropic conversion, which not only retains the disinfection and sterilization effect of the original iodine preparation, but also the two-dimensional structure before the conversion effectively avoids the uncontrollability of iodine solution as a fluid, and slowly releases the antibacterial effect for a long time, and can be used as a drug to sterilize and disinfect the infection site to avoid regional bacterial infection.

[0019] (3) The present invention combines hydrogel with iodine nanosheet material, which not only maximizes the antibacterial effect, but also has high plasticity and small tissue rejection reaction, and has the advantages of not requiring a second-stage operation to remove the stent material.

[0020] In summary, the present invention, on the one hand, exerts antibacterial effect by loading antibacterial material iodine nanosheets I2, reduces the probability of bacterial infection at the infection site and has no bacterial resistance; on the other hand, by using plastic composite hydrogel as a loading system, the product has excellent properties such as plasticity, stretchability, self-healing, adhesion, and degradability, which is convenient for filling defective parts of various shapes and firmly attached. Therefore, it is very practical and suitable for wide promotion. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 The scanning electron micrographs of PBST hydrogel and PBST / I2 plastic antibacterial composite hydrogel; (a) PBST hydrogel at a scale of 300 μm, (b) PBST / I2 composite hydrogel at a scale of 300 μm, (c) PBST hydrogel at a scale of 100 μm, and (d) PBST / I2 composite hydrogel at a scale of 3 μm;

[0022] Figure 2 The gelation diagrams of PBST hydrogel and PBST / I2 plastic antibacterial composite hydrogel; (a) PBST hydrogel tilted state diagram, (b) PBST / I2 composite hydrogel tilted state diagram, (c) PBST hydrogel inverted state diagram, (d) PBST / I2 composite hydrogel inverted state diagram;

[0023] Figure 3 Physical and chemical properties of PBST / I2 plastic antibacterial composite hydrogel: (a) pH sensitivity, (b) adhesion, (c) stretchability, (d) plasticity and (e) self-healing test diagram.

[0024] Figure 4 The antibacterial effect diagram of PBST / I2 plastic antibacterial composite hydrogel; (a) inhibition effect of Escherichia coli; (b) inhibition effect of Staphylococcus aureus. DETAILED DESCRIPTION

[0025] The present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.

[0026] All raw materials and reagents in the examples of the present application were purchased on the market or prepared according to conventional methods well known to those skilled in the art.

[0027] Comparative Example 1

[0028] A method for preparing a hydrogel comprises the following steps:

[0029] S1. Under the conditions of magnetic stirring (speed of 300r) and heating in a water bath at 90°C, dissolve 0.85g of polyvinyl alcohol to 10.6mL with double distilled water at 90°C and continue heating in a water bath until the polyvinyl alcohol is completely dissolved to obtain a polyvinyl alcohol solution, add 300mg of sodium alginate to the polyvinyl alcohol solution in 4 to 5 times, continue stirring under magnetic stirring (speed of 300r) and 90°C water bath for 1h, and obtain a plastic composite hydrogel precursor solution;

[0030] S2, adding tannic acid to the plastic composite hydrogel precursor solution prepared in step S1, continuing magnetic stirring (speed of 300r) at room temperature for uniform mixing, and dropping sodium hydroxide standard solution to adjust the pH value to neutral;

[0031] S3, adding borax solution (87.387 mg of borax is dissolved in deionized water to 3 mL to prepare borax solution) to the solution obtained in step S2 and stirring to form a gel to obtain PBST hydrogel, the scanning electron microscopy of which is as follows Figure 1 a and Figure 1 c, the macroscopic picture is as follows Figure 2 a and Figure 2 As shown in c.

[0032] from Figure 1 a and Figure 1 c It can be seen that the PBST hydrogel microstructure is porous, which is conducive to cell adhesion and tissue fluid infiltration, and is an ideal scaffold material; Figure 2 a and Figure 2 c It can be seen that the macroscopic structure of the PBST hydrogel is yellow-white colloid, has good adhesion and is not fluid; compared with Example 1, since no iodine nanosheets are added, the iodine nanosheet particles are not visible microscopically, the macroscopic color is lighter, and it does not yet have strong antibacterial properties.

[0033] Example 1

[0034] A method for preparing a plastic antibacterial composite hydrogel loaded with iodine nanosheets comprises the following steps:

[0035] S1. Prepare iodine nanosheet suspension: weigh 1g iodine, weigh and record the mass of a 50mL centrifuge tube; use a mortar to fully grind the iodine block into powder, put it into a centrifuge tube, add 50mL of double distilled water, and place it in an ultrasonic cleaner for ultrasonic peeling for 4 hours. Centrifuge the turbid liquid after ultrasonic peeling at a speed of 12000r for 30min, take the supernatant, and put the precipitate and the centrifuge tube into an oven for drying; after it is dried, weigh it. Remove the iodine that has not dissolved after centrifugation to obtain a 5mg / mL iodine nanosheet suspension in the supernatant;

[0036] S2. Prepare a plastic composite hydrogel precursor solution: dissolve 0.85 g of polyvinyl alcohol to 10.6 mL in double distilled water at 90° C. under magnetic stirring (rotation speed of 300 r) and heating in a 90° C. water bath, and continue heating in a water bath until the polyvinyl alcohol is completely dissolved to obtain a polyvinyl alcohol solution, add 300 mg of sodium alginate to the polyvinyl alcohol solution in 4 to 5 portions, continue stirring under magnetic stirring (rotation speed of 300 r) and 90° C. water bath for 1 h, and obtain a plastic composite hydrogel precursor solution;

[0037] S3, dissolving 200 mg of tannic acid with 5 mg / mL of iodine nanosheet suspension to 5 mL to obtain a tannic acid-I2 composite solution, then adding the tannic acid-I2 composite solution to the plastic composite hydrogel precursor solution prepared in step S2, continuing magnetic stirring (speed of 300r) at room temperature for uniformity, and dropping a sodium hydroxide standard solution to adjust the pH value to neutral;

[0038] S4, dropwise add borax solution (87.387 mg borax is dissolved in deionized water to 3 mL to prepare borax solution) to the solution obtained in step S3 and stir to form a gel to obtain I2 / PBST moldable antibacterial composite hydrogel, as shown in the scanning electron microscope. Figure 1 b and 1d, the macroscopic picture is as follows Figure 2 b and Figure 2 As shown in d.

[0039] from Figure 1 b and Figure 1 d As can be seen, iodine nanosheet particles can be seen in the I2 / PBST shapeable antibacterial composite hydrogel under scanning electron microscopy; Figure 2 b and Figure 2 d It can be seen that the I2 / PBST shapeable antibacterial composite hydrogel is brown-yellow colloid, has strong adhesion and no fluidity; compared with the control example, the I2 / PBST shapeable antibacterial composite hydrogel has better antibacterial properties.

[0040] The composite hydrogel prepared in this example was tested for pH sensitivity, adhesion, stretchability, plasticity, and self-healing properties: equal volumes of the composite hydrogel were placed in pH = 5.5, pH = 6, pH = 6.5, and 15% hydrochloric acid for pH sensitivity testing. The results are shown in Table 1. Figure 3 The composite hydrogel shown in (a) can maintain a complete gel state in an environment with a pH of 5.5, 6, and 6.5, but will dissolve in 15% hydrochloric acid. The composite hydrogel is placed on the finger and moved, such as Figure 3 (b) The hydrogel adheres firmly to the finger, verifying that the composite hydrogel has adhesion. 2 The composite hydrogel is stretched from 1 cm to the limit, such as Figure 3(c) shows a measurement of 40 cm, which verifies that the composite hydrogel has strong stretchability; Figure 3 As shown in (d), the composite hydrogel can be molded into a variety of shapes, verifying its strong plasticity; the composite hydrogel is cut and the ends are brought into contact for 30 to 60 seconds. Figure 3 (e) The broken ends healed, verifying its self-healing property.

[0041] The composite hydrogel prepared in this example was tested for its antibacterial effect: 30 μL of bacterial suspension of Escherichia coli and Staphylococcus aureus and 270 μL of LB liquid culture medium were mixed and added to the surface of the moldable antibacterial composite hydrogel, and cultured in a 37°C incubator for 3 hours. The control group was a blank well. 100 μL of the diluted bacterial solution was inoculated on the agar plate, and then cultured in a 37°C incubator for 12 hours to observe and calculate the antibacterial rate; the results are shown in Figure 2. Figure 4 (a) and Figure 4 As shown in (b), it can be seen from the figure that after the colony culture of Escherichia coli (4a) and Staphylococcus aureus (4b), the colony counts of the PBST group in both bacterial experiments were reduced compared with the blank group, while the colony counts in the PBST / I2 group were the least, and the antibacterial rates of Escherichia coli and Staphylococcus aureus were both above 90%. This indicates that the addition of iodine nanosheets to PBST significantly enhanced the antibacterial effect, further proving the antibacterial properties of the composite hydrogel.

[0042] Example 2

[0043] The present embodiment is different only in the content of tannic acid in step S3: "160 mg of tannic acid is dissolved to 4 mL with 5 mg / mL iodine nanosheet suspension to obtain a tannic acid-I2 composite solution", and the other steps are kept consistent with Example 1.

[0044] Example 3

[0045] The present embodiment is different only in the content of tannic acid in step S3: "80 mg of tannic acid is dissolved to 2 mL with 5 mg / mL iodine nanosheet suspension to obtain a tannic acid-I2 composite solution", and the other steps are kept consistent with Example 1.

[0046] Referring to Example 1, the composite hydrogels prepared in Example 2 and Example 3 were respectively subjected to pH sensitivity, adhesion, stretchability, plasticity, self-healing test and antibacterial effect test, and the test results were similar to those in the example.

[0047] For those skilled in the art, the present invention is not limited to the details of the exemplary embodiments described above. The embodiments are exemplary and non-restrictive, and the scope of protection of the present invention is defined by the appended claims rather than the above description, and therefore, any reference numerals in the claims should not be regarded as limiting the claims involved.

Claims

1. A method for preparing a plastic antibacterial composite hydrogel loaded with iodine nanosheets, characterized in that: The following steps are involved: S1. preparing iodine nanosheet suspension: grinding iodine block to obtain iodine powder, adding iodine powder to double distilled water, ultrasonically peeling, centrifuging, and taking the supernatant as iodine nanosheet suspension; S2. Preparing a plastic composite hydrogel precursor solution: dissolving polyvinyl alcohol with double distilled water at 85 to 95° C. under stirring and heating in a water bath at 85 to 95° C., and obtaining a polyvinyl alcohol solution after the polyvinyl alcohol is completely dissolved, adding sodium alginate in batches, and continuing to stir in a water bath at 85 to 95° C. for 0.5 to 1.5 h to obtain a plastic composite hydrogel precursor solution; S3, using the iodine nanosheet suspension prepared in step S1 to dissolve tannic acid to obtain a tannic acid-I2 composite solution, then adding the tannic acid-I2 composite solution to the plastic composite hydrogel precursor solution prepared in step S2, stirring evenly at room temperature, and adjusting the pH value of the solution to neutral; S4, adding borax solution to the solution obtained in step S3 and stirring to form a gel to obtain I2 / PBST shapeable antibacterial composite hydrogel.

2. The method for preparing a plastic antibacterial composite hydrogel loaded with iodine nanosheets according to claim 1, characterized in that: In step S1, the concentration of the iodine nanosheet suspension is 5 mg / mL; the suspension is placed in an ultrasonic cleaner for ultrasonic peeling for 4 hours.

3. The method for preparing a plastic antibacterial composite hydrogel loaded with iodine nanosheets according to claim 1 or 2, characterized in that: In step S2, the mass fraction of the polyvinyl alcohol solution is 8%; the mass volume ratio between the sodium alginate and the polyvinyl alcohol solution is 30 mg:1.06 mL.

4. The method for preparing a plastic antibacterial composite hydrogel loaded with iodine nanosheets according to claim 1 or 2, characterized in that: In step S2, polyvinyl alcohol is dissolved in 90° C. double distilled water under stirring and heating in a 90° C. water bath. After the polyvinyl alcohol is completely dissolved, sodium alginate is added in batches and stirring is continued in a 90° C. water bath for 1 hour to obtain a shapeable composite hydrogel precursor solution.

5. The method for preparing a plastic antibacterial composite hydrogel loaded with iodine nanosheets according to claim 1 or 2, characterized in that: In step S3, the concentration of the tannic acid-I2 composite solution is 40 mg / mL; the volume ratio between the tannic acid-I2 composite solution and the shapeable composite hydrogel precursor solution is 1:2.12-5.

30.

6. The method for preparing a plastic antibacterial composite hydrogel loaded with iodine nanosheets according to claim 1 or 2, characterized in that: In step S4, the concentration of the borax solution is 29 mg / mL; the volume ratio between the borax solution and the shapeable composite hydrogel precursor solution in step S2 is 1:3.

53.

7. A shapeable antibacterial composite hydrogel loaded with iodine nanosheets prepared by the preparation method according to any one of claims 1 to 6.

Citation Information

Cited By

  • Application of two-dimensional iodine nanosheet in preparation of antibacterial material

    CN116036124A